PENERAPAN PENDEKATAN SAINTIFIK UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI PERPINDAHAN PANAS SECARA KONDUKSI DI KELAS V SDK ST. YOSEPH 4 NAIKOTEN 2 KOTA KUPANG - Blandina Agnes Funan; Maxsel Koro; Netty E.A. Nawa (Universitas Nusa Cendana, 2023)
The scientific approach is one of the approaches in classroom learning activities to accommodate the needs of students in learning. The topic of heat transfer by conduction includes knowledge (science products) and science process skills which in order to study them require an appropriate and efficient approach according to the characteristics of the material. The purpose of this study was to improve the learning outcomes of grade 5 students on heat transfer by conduction. This study applies a class action research design. The subjects of this study were 34 grade 5 students at SDK St. Joseph 4 Kupang City. Data collection was carried out by means of observation and learning achievement tests. The instruments used were questionnaires and learning outcomes test questions totaling 10 multiple-choice questions. The results showed that the results of the action test in cycle I obtained the percentage of student learning activity of 72.45% and the percentage of students who completed the test results were 17 students with a percentage of 50% and the number of students who did not complete 17 students with a percentage of 50%. Cycle II obtained the percentage of student learning activities on average 88.7% and the percentage of student learning outcomes that were completed was 32 students with a percentage of 94.1%. However, the number of students who did not complete was 2 students with a percentage of 5.9%. Based on the results of cycles I and II, it can be concluded that the application of a scientific approach can improve student learning outcomes in grade 5 at SDK St. Joseph 4 Kupang City.